Cubic Spinel XIn2S4 (X = Fe, Co, Mn): A New Type of Anode Material for Superfast and Ultrastable Na‐Ion Storage. Issue 44 (7th October 2021) - Yan, Dong; Li, Ke; Yan, Yaping; Huang, Shaozhuan; Von Lim, Yew; Shang, Yang; Fang, Daliang; Ang, Lay Kee; Yang, Hui Ying
Abstract: Bimetallic sulfides are prospective candidates as Na‐ion battery (NIB) anodes owing to their abundant redox active sites and high specific capacities, while the rate and cycling performances are limited due to their severe mechanical strain and sluggish reaction kinetics. Herein, for the first time, a series of cubic spinel XIn2 S4 (X = Fe, Co, Mn) anodes is proposed for superfast and ultrastable Na‐ion storage. The FeIn2 S4 delivers the best electrochemical performance among them with the amazing results especially for its superfast charging (9–13 s per charge with ≈300 mAh g −1 input) and ultrastable cycling capabilities (25 K cycles with ultralow 0.000801% capacity loss per cycle). Further density functional theory calculations and experimental results indicate that Fe substitution at tetrahedral sites of cubic spinel In2.77 S4 can significantly enhance its electrical conductivity, Na‐ion binding kinetics, and pseudocapacitive contributions, reduce its Na‐ion diffusion barrier, and relieve its mechanical strain. Moreover, the inherent In skeleton at octahedral sites can induce a complementary reaction to stabilize the conversion‐type Fe‐based components. Furthermore, the FeIn2 S4 ‐based full cells with excellent electrochemical performance are assembled. This work demonstrates the feasibility of enhancing the synergies within bimetallic sulfides to realize remarkable electrochemical performance. Abstract : For the first time, a new type of cubic spinel XIn2 S4 (X = Fe, Co, Mn) anode is proposed for superfast and ultrastable Na‐ion storage. The significant optimization effect on electrochemical performance induced by the X substitution at tetrahedral sites of cubic spinel In2.77 S4 contributes to the amazing results, which transcend most of the other reported advanced anodes in Na‐ion batteries.